Changes of ecotopic characteristics in «Yelanets Steppe» Reserve during the first decade since being established (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
This paper is to continue and amplify the previous report on structural changes of vegetation in Natural Reserve «Yelanets’ky steppe» (1675.7 ha, Mykolayiv, Ukraine). Synphytoindicative assessment of the Reserve was made for the two different time spans with 10 years gap (1997-2007). An ordination of phytoindicative parameters of main communities and different coenotic combinations was executed. The most of steppes and petrophytic communities are distributed in the zone of very limited water supply. An assumption of destroying impact of frequent fires on steppe vegetation was confirmed. Total range of water supply in the reserve is very large, but the main part of it covers lowchanging ecotopes of deep depressions with intrazonal vegetation. There were also strengthening of the soil carbonate content, enrichment of pedosphere with salts, and reduction of the content of nitrogen compounds in soils. Ecotopic changes in «Yelanets’ky Steppe» habitats were unfavorable for the renewal (demutation) of vegetation. Only general aridisation could cause such direction of changes with intrazonal ecotopes of gully bottoms contrasted with plakor-zonal ones.
Keywords: steppe reserve, first decade of reservation, synphytoindication, fires, drought, changes of ecotopic features.